Reducing Nontraumatic Lower-Extremity Amputations by 20% by 2030: Time to Get to Our Feet: A Policy Statement From the American Heart Association. Issue 17 (25th March 2021) - Creager, Mark A.; Matsushita, Kunihiro; Arya, Shipra; Beckman, Joshua A.; Duval, Sue; Goodney, Philip P.; Gutierrez, J. Antonio T.; Kaufman, John A.; Joynt Maddox, Karen E.; Pollak, Amy W.; Pradhan, Aruna D.; Whitsel, Laurie P.
Abstract : Nontraumatic lower-extremity amputation is a devastating complication of peripheral artery disease (PAD) with a high mortality and medical expenditure. There are ≈150 000 nontraumatic leg amputations every year in the United States, and most cases occur in patients with diabetes. Among patients with diabetes, after an ≈40% decline between 2000 and 2009, the amputation rate increased by 50% from 2009 to 2015. A number of evidence-based diagnostic and therapeutic approaches for PAD can reduce amputation risk. However, their implementation and adherence are suboptimal. Some racial/ethnic groups have an elevated risk of PAD but less access to high-quality vascular care, leading to increased rates of amputation. To stop, and indeed reverse, the increasing trends of amputation, actionable policies that will reduce the incidence of critical limb ischemia and enhance delivery of optimal care are needed. This statement describes the impact of amputation on patients and society, summarizes medical approaches to identify PAD and prevent its progression, and proposes policy solutions to prevent limb amputation. Among the actions recommended are improving public awareness of PAD and greater use of effective PAD management strategies (eg, smoking cessation, use of statins, and foot monitoring/care in patients with diabetes). To facilitate the implementation of these recommendations, we propose several regulatory/legislative and organizational/institutional policies such as adoption of quality measures for PAD care; affordable prevention, diagnosis, and management; regulation of tobacco products; clinical decision support for PAD care; professional education; and dedicated funding opportunities to support PAD research. If these recommendations and proposed policies are implemented, we should be able to achieve the goal of reducing the rate of nontraumatic lower-extremity amputations by 20% by 2030.